Measurement of J/[psi] production in association with a W-+ boson with pp data at 8 TeV - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Bolz, Arthur; Brandt, Oleg; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Giulini, Maddalena; et al. (Journal of high energy physics, 2020)
A measurement of the production of a prompt J/psi meson in association with a W-+/- boson with W-+/- -> mu nu and J/psi -> mu(+)mu(-) is presented for J/psi transverse momenta in the range 8.5-150 GeV and rapidity |y(J/psi)| < 2.1 using ATLAS data recorded in 2012 at the LHC. The data were taken at a proton-proton centre-of-mass energy of s = 8 TeV and correspond to an integrated luminosity of 20.3 fb(-1). The ratio of the prompt J/psi plus W-+/- cross-section to the inclusive W-+/- cross-section is presented as a differential measurement as a function of J/psi transverse momenta and compared with theoretical predictions using different double-parton-scattering cross-sections.